Bunny Should Be Sleeping - Hest, Amy; Liwska, Renata (New York : Holiday House, 2024)
When Dad forgets to check on Bunny one night, Bunny gets up to check on Dad.
"Neal Porter Books."
new kids book 2024 summer.
Ages 4-8.
Grades K-1.
Keywords: Father and child -- Juvenile fiction; Bedtime -- Juvenile fiction; Rabbits -- Juvenile fiction; Fathers and sons -- Juvenile fiction; Animal fiction; Picture books